If my cholesterol is…then I foresee…: patient accounts of uncertainty - Darlene K. Drummond (Qualitative Research in Medicine & Healthcare)
The author examines the talk of patients with high cholesterol as they discuss their experiences of adding a statin to their treatment regimen. The primary objective was to understand patients’ expectations of statins, and their beliefs and feelings as they continued or discontinued use, and to better understand why adherence to a statin regimen is particularly low. While numerous studies report reasons for nonadherence, few apply theory to provide plausible explanations. Analysis of the focus group data revealed three major themes. First, patients do not view high cholesterol as serious in light of other major health problems like diabetes and cancer within the household. Second, patients believe statins are effective in lowering cholesterol but risky. Third, many patients do not understand how high levels of cholesterol are produced in the body and how statins interrupt that process. Problematic integration theory is used to explain the uncertainty patients experience when given a diagnosis of high cholesterol, the use of statins to control it, and the quality of information received about both cholesterol and statins.